Safety of ACE-I and ARB medications in COVID-19: A retrospective cohort study of inpatients and outpatients in California. Issue 1 (1st June 2020) - Rubin, Samuel J. S.; Falkson, Samuel R.; Degner, Nicholas R.; Blish, Catherine A.
Abstract: Introduction: There is significant interest in the use of angiotensin converting enzyme inhibitors (ACE-I) and angiotensin II receptor blockers (ARB) in coronavirus disease 2019 (COVID-19) and concern over potential adverse effects since these medications upregulate the severe acute respiratory syndrome coronavirus 2 host cell entry receptor ACE2. Recent studies on ACE-I and ARB in COVID-19 were limited by excluding outpatients, excluding patients by age, analyzing ACE-I and ARB together, imputing missing data, and/or diagnosing COVID-19 by chest computed tomography without definitive reverse transcription polymerase chain reaction (RT-PCR), all of which are addressed here. Methods: We performed a retrospective cohort study of 1023 COVID-19 patients diagnosed by RT-PCR at Stanford Hospital through April 8, 2020 with a minimum follow-up time of 14 days to investigate the association between ACE-I or ARB use with outcomes. Results: Use of ACE-I or ARB medications was not associated with increased risk of hospitalization, intensive care unit admission, or death. Compared to patients with charted past medical history, there was a lower risk of hospitalization for patients on ACE-I (odds ratio (OR) 0.43; 95% confidence interval (CI) 0.19–0.97; P = 0.0426) and ARB (OR 0.39; 95% CI 0.17–0.90; P = 0.0270). Compared to patients with hypertension not on ACE-I or ARB, patients on ARB medications had a lower risk of hospitalization (OR 0.09; 95% CI 0.01–0.88; P = 0.0381). Conclusions: These findings suggest that the use of ACE-I and ARB is not associated with adverse outcomes and may be associated with improved outcomes in COVID-19, which is immediately relevant to care of the many patients on these medications.